2010
DOI: 10.1111/j.1475-6811.2010.01302.x
|View full text |Cite
|
Sign up to set email alerts
|

Market value, quality of the pool of potential mates, and singles' confidence about marrying

Abstract: Although most mate selection research has focused on what people want in a marriage partner, this research focuses on what people think they can get. Using survey data from a large, representative sample of unmarried individuals, this study revealed that people who believed they possessed fewer qualities that are valued in the mating marketplace and who reported meeting lower quality potential mates felt less confident about their chances of securing an acceptable partner to marry; these associations were no w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
20
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 53 publications
3
20
1
Order By: Relevance
“…As described in the previous sections, both theory and qualitative work (e.g., Lewis & Moon, 1997) suggest that individuals' criteria for a spouse are "realistic" to the extent that they reflect both their own overall desirability as a long-term partner and their access to desirable prospective mates. Although numerous studies have shown that, on average, people's spousal standards are positively associated with their mate value and with the availability of high-quality partners (e.g., Bredow et al, 2011;Kenrick et al, 1993;Sprecher & Regan, 2002), there is often considerable variation in the extent to which individuals' reported standards reflect their mating constraints (Bredow & Huston, 2009;Pawlowski & Dunbar, 1999). Whereas some people's standards closely approximate their opportunity structure, others' criteria are notably higher than would be expected given their social desirability and partnering context.…”
Section: Overview Of the Current Investigationmentioning
confidence: 99%
See 4 more Smart Citations
“…As described in the previous sections, both theory and qualitative work (e.g., Lewis & Moon, 1997) suggest that individuals' criteria for a spouse are "realistic" to the extent that they reflect both their own overall desirability as a long-term partner and their access to desirable prospective mates. Although numerous studies have shown that, on average, people's spousal standards are positively associated with their mate value and with the availability of high-quality partners (e.g., Bredow et al, 2011;Kenrick et al, 1993;Sprecher & Regan, 2002), there is often considerable variation in the extent to which individuals' reported standards reflect their mating constraints (Bredow & Huston, 2009;Pawlowski & Dunbar, 1999). Whereas some people's standards closely approximate their opportunity structure, others' criteria are notably higher than would be expected given their social desirability and partnering context.…”
Section: Overview Of the Current Investigationmentioning
confidence: 99%
“…By reducing measurement error in the variables, using a multi-informant, multi-indicator approach to assess people's mate value and the favorability of their marriage markets allows me to best capture the "reality" of people's opportunity structures -and thus the type of partner they are likely to secure. Based on past research suggesting that singles' mate value and mating market quality are generally interrelated (Bredow et al, 2011), these two constructs are presumed to be correlated in the model. A latent interaction term (i.e., Mate Value × Mate Availability) is also included to assess the possibility that the strength of the association between people's own desirability as a marriage partner and the stringency of their mate standards may depend upon the availability of desirable potential partners (and vice versa).…”
Section: Overview Of the Current Investigationmentioning
confidence: 99%
See 3 more Smart Citations